Design, synthesis and structure–activity relationship of novel oxime ether strobilurin derivatives containing substituted benzofurans. Issue 3 (28th May 2014) - Xie, Ya‐Qiang; Huang, Yi‐Bing; Liu, Jian‐She; Ye, Li‐Yi; Che, Li‐Ming; Tu, Song; Liu, Chang‐Ling
Abstract BACKGROUND Strobilurins are one of the most important classes of agricultural fungicides. To discover new strobilurin analogues with broad spectrum and high activity, a series of novel oxime ether strobilurin derivatives containing substituted benzofurans in the side chain were synthesised and bioassayed. RESULTS The synthesised compounds were characterised by 1H NMR, 13C NMR, MS and HRMS. Bioassays demonstrated that most target compounds possessed good or excellent fungicidal activities, especially against Erysiphe graminis and Pyricularia oryzae. Furthermore, methyl 3‐methoxypropenoate oxime ethers exhibited remarkably higher activities against E. graminis, Colletotrichum lagenarium and Puccinia sorghi Schw. Notably, (E, E)‐methyl 3‐methoxy‐2‐2‐[([5‐fluoro‐1‐(benzofuran‐2‐yl)ethylidene]aminooxy)methyl]phenylpropenoate (BSF2) and (E, E)‐methyl 3‐methoxy‐2‐2‐[([5‐chloro‐1‐(benzofuran‐2‐yl)ethylidene]aminooxy)methyl]phenylpropenoate (BSF3) were identified as the most promising candidates for further study. CONCLUSION The present work demonstrates that oxime ether strobilurin derivatives containing benzofurans can be used as possible lead compounds for developing novel fungicides. © 2014 Society of Chemical Industry